Intramedullary Versus Extramedullary Tibial Alignment Guides in Total Knee Arthroplasty: A Radiographic Analysis - Nualsalee, MD, Nitiphol; Sumettavanich, MD, Charlee (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: to evaluate the postoperative radiographic position of the TKA components and compare the difference in the accuracy of positioning of tibial components between Intramedullary guides tibia and extramedullary guides tibia. Methods: An intramedullary guide was used in 50 cases and extramedullary guide was used in another 50 cases. A radiographic study was performed after 3 month of follow up to evaluate postoperative component position and compare the difference in the tibiofemoral angle and the tibial component angle between 2 groups. Results: Radiographic analysis showed that satisfactory position was achieved using both types of instrumentation. No statistically significant difference was observed in the tibiofemoral angle. However the coronal plane positioning of the tibial component revealed a statistically significant difference (p < 0.01), with intramedullary guides being superior to extramedullary guides. Both groups were within the percentage of outlier (< 3 degree varus). The mean surgery time and the drainage blood loss in intramedullary guides was more than extramedullary guides with statistically significant difference (p < 0.01). Conclusion: Both techniques allowed satisfactory alignment. It is important for the surgeon to appreciate the benefits and deficiencies of each guide and to use whichever is suited most properly in each particular case.